Internal deformation of the Shan-Thai block inferred from paleomagnetism of Jurassic sedimentary rocks in Northern Thailand - Kazuyoshi Aihara (2018)
Paleomagnetic samples of red sandstones were collected at 16 sites from the Lower to Upper Jurassic Phu Kradung formation and the Upper Jurassic Phra Wihan formation around Nan City (19.2°N, 101.0°E) in the southern region of the Shan-Thai block. After stepwise thermal demagnetization, a high-temperature component with an unblocking temperature of about 680 °C is isolated from 11 sites. We interpret this to be a prefold characteristic remanent magnetization because of a positive fold test at the 95% confidence level. The tilt-corrected mean paleomagnetic direction from 11 sites is D = 32.3°, I = 33.3°, α95= 12.2°, k = 15.0, which gives a paleomagnetic pole for this area of 60.1°N, 186.5°E with A95= 11.7°. Compared with a Jurassic paleopole for the stable part of the Yangtze block, we observe a clockwise tectonic rotation of 12.8°, which is similar to the observed rotation (18-28°) of the northern region of the Shan-Thai block. This amount contrasts with a large rotation of more than 45° that is estimated from the narrow zone extending from Luxi to Mengla in the central region of this block. This declination aspect suggests that a coherent whole block rotation by about 20° of the Shan-Thai block took place in an earlier phase during indentation of India into Asia and that an internal deformation with additional local rotation between 25° and 77° followed within a limited zone in the central part. The internal deformation of the Shan-Thai block absorbed the stress on the Asian continent induced by indentation of India as well as its coherent whole block motions of clockwise rotation and southward displacement. © 2007 Elsevier Ltd. All rights reserved.